Progressive damage and failure analysis of single lap shear and double lap shear bolted joints. (October 2018) - Joseph, Ashith P.K.; Davidson, Paul; Waas, Anthony M.
Abstract: Intra-inter crack band model (I2CBM) is proposed for studying the progressive damage and failure of laminated composite bolted joints. The model combines Schapery theory for matrix microcrack modeling with crack band theory for lamina macroscopic failure modeling in a standard 3D finite element framework and is implemented as material laws at element integration points. Three different failure planes defined by material orthotropy are considered for the modeling of macroscopic failure using crack band theory. This procedure allows the model to be used either as an intraply element or as an interply element of finite thickness by an appropriate choice of the crack planes of interest. Localized bearing failure, observed in bolted joints, is modeled using a residual strength approach in the post-peak response of individual ply elements. Simulation results for single lap shear and double lap shear bolted joint problems are compared against experiments for model validation.